APLIKASI BERBASIS WEB UNTUK PUBLIKASI PRODUK INOVASI DAN PENELITIAN DI POLITEKNIK NEGERI INDRAMAYU - Dimas Arya Ramadhan Setiawan; Andre Wibowo; Arifin Nurhidayah; Robieth Sohiburoyyan (Journal of Informatics and Computing, 2025)
Advances in information technology provide opportunities for educational institutions to publish research results and innovation products more effectively. Politeknik Negeri Indramayu, as a vocational institution, needs a platform that is able to optimally manage and disseminate innovation and research products. This research aims to develop a web-based application that supports the publication of innovation and research work, while increasing accessibility and collaboration among researchers, students, and the general public. The application is designed using the Agile Development approach, utilizing the Laravel framework for the backend and Bootstrap for the frontend, resulting in a responsive and multiplatform system. Key features include innovation catalog management, research data search, and an interactive dashboard for user-friendly administration. The platform allows innovation and research data to be displayed in a structured manner and can be accessed easily by various parties. The use of this application is expected to have a significant impact on the visibility of Indramayu State Polytechnic's innovative work. In addition, this application can also be integrated with social media and academic portals to expand the reach of publications. Thus, this application is not only an efficient data management solution but also supports Indramayu State Polytechnic in increasing competitiveness at the national and international levels.